The effects of substrate orientation on galvanic growth of ZnO structures - Kuan, Ying Kok; Inn, Khuan Ng; Nur Ubaidah, Saidin; Thye, Foo Choo; Boon, Siong Wee; Yusof, Abdullah (Trans Tech Publications Ltd, 2017)
Electrochemical route has been a favorite technique for the fabrication of ZnO as it is relatively cheap and capable of producing abundance amount of materials. In this paper, we investigate the morphologies of hydrothermally synthesized ZnO structures assisted by galvanic process on conducting Au-coated silicon substrate. To induce the galvanic process, the substrate was in contact with aluminum so that the difference in the reduction potentials between the two materials provided the driving force for the formation of the ZnO structures. The galvanic process was found to promote compact and anisotropy growth of ZnO nanorods along the (001) plane. It was also found that substrate orientations in the electrolyte solution had an important bearing on the morphologies of ZnO. Well aligned periodic hexagonal arrays of ZnO nanorods of homogeneous diameters were obtained on gold-coated Si substrate with face-down orientation in the electrolyte solution.